2017
DOI: 10.1080/07357907.2017.1364745
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the Potential of Vascular Targeted Therapy: The Rationale for Combining Vascular Disrupting Agents and Anti-Angiogenic Agents to Treat Cancer

Abstract: Vascular targeted therapies (VTTs) are agents that target tumor vasculature and can be classified into two categories: those that inhibit angiogenesis and those that directly interfere with established tumor vasculature. Although both the anti-angiogenic agents (AAs) and the vascular disrupting agents (VDAs) target tumor vasculature, they differ in their mechanism of action and therapeutic application. Combining these two agents may realize the full potential of VTT and produce an effective therapeutic regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 141 publications
0
55
0
Order By: Relevance
“…The expression levels of the angiogenic growth factors were shown to impact tumor progression. These angiogenic factors are upregulated by a variety of mechanisms like oncogene activation, loss of tumor suppressor gene function, and/or hypoxic microenvironments [40]. Moreover, fibroblast growth factor receptor (FGFR) modulates a series of angiogenic processes which includes FGF-mediated glioma endothelial cell migration and proliferation.…”
Section: Factors Involved In Brain Tumor Angiogenesismentioning
confidence: 99%
“…The expression levels of the angiogenic growth factors were shown to impact tumor progression. These angiogenic factors are upregulated by a variety of mechanisms like oncogene activation, loss of tumor suppressor gene function, and/or hypoxic microenvironments [40]. Moreover, fibroblast growth factor receptor (FGFR) modulates a series of angiogenic processes which includes FGF-mediated glioma endothelial cell migration and proliferation.…”
Section: Factors Involved In Brain Tumor Angiogenesismentioning
confidence: 99%
“…With VDAs, the vascular damage induced causes a reduction in tumor blood flow and this increases the adverse microenvironmental conditions within tumors leading to substantial cell killing and subsequent increase in necrosis (82,84,85). The overall result is a reduction in tumor volume.…”
Section: Vascular Targeting Agents and Hypoxiamentioning
confidence: 99%
“…This stabilization process was termed "normalization" (86) and the more stable, organized vasculature that resulted would likely lead to a better delivery of oxygen and nutrients to the tumor, thus reducing the degree of tumor hypoxia. Numerous studies have since reported that treatment with a range of AIs can indeed give rise to an apparent decrease in tumor hypoxia (82,84). The first study that demonstrated an improvement in oxygenation status that was associated with vessel normalization was that of Winkler and colleagues (87), using the anti-VEGF (vascular endothelial growth factor) monoclonal antibody DC101.…”
Section: Vascular Targeting Agents and Hypoxiamentioning
confidence: 99%
“…Tumor endothelial cells are more accessible to systemically delivered agents than tumor cells in solid organ cancers and are less likely to develop resistance to therapies than neoplastic cells . In this context, treatment aimed toward the endothelium, including tubulin‐targeted drugs, may have an amplifying anti‐tumor effect . Hierarchical blood vessel organization, a hallmark of normal tissue vasculature, is lost in tumors.…”
Section: Tumor Endothelial Cellsmentioning
confidence: 99%